(untitled) (Our Nature, 2015)
During taxonomical study of Coleochaete Bréb., an epiphytic alga, three species viz. Coleochaete nitellarum Jost, Coleochaete pulvinata A. Br. ex Kütz., Coleochaete soluta (Bréb.) Pringsh. belonging to the order Chaetophorales under the class Chlorophyceae were recorded in the winter season from three sites of Hooghly district in West Bengal, India. The thallus of C. nitellarum grew diffusely on the submerged angiospermic plants and consists of irregularly branched prostrate filaments. In C. soluta, the erect filaments were freely branched while, upper cells of erect filaments were cylindrical and thallus was hemispherical in C. pulvinata. The most important finding of the limnological work was the higher concentration of DO in the lentic aquatic ecosystems where they occurred that might be due to higher rate of photosynthetic activities and lower temperature of water. This study also exhibited somewhat, lower nutrient status in respect of NO3-N: PO43-: K ratios. The review of literatures revealed that C. pulvinata was the second time report and other two taxa were reported third timely from this state. Our Nature (2015), 13(1): 19-25